Pravove zabezpečennâ konkurenciї u trudovih pravovìdnosinah - Rim, Olena (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2011)
The article deals with comprehensive research of problems of the legal providing of competition in legal labour relations. The propositions concerning these problems resolving are made. The peculiarities of the legal regulation of the prevention of competition in legal labour relations in the foreign countries are described. The notion of unfair competition in the legal labour relations is disclosed, the forms of its display and the methods of its prevention are analysed.In the article the analysis of the valid domestic legislation that govern the prevention of competition in labour relations is made. The author stresses the necessity of using the experience of foreign countries with developed market economy in regulating these legal relations in the domestic labour law. In particular, she proposes to adopt in the Labour Code of Ukraine provision that would prohibit an employee to disclose trade secrets of the employer during the time of the employment contract validity and after its termination for the duration of intellectual property rights on trade secrets.
Keywords: Ukraina; stosunki pracy; konkurencja; podstawy prawne konkurencji